Full-length transcriptome sequencing provides insights into alternative splicing under cold stress in peanut - Wang, Xin; Liu, Yue; Ouyang, Lei; Yao, Ruonan; Yu, Tingting; Yan, Liying; Chen, Yuning; Huai, Dongxin; Zhou, Xiaojing; Wang, Zhihui; Kang, Yanping; Wang, Qianqian; et al. (Frontiers in Plant Science, 2024)
Peanut (Arachis hypogaea L.), also called groundnut, is an important oil and cash crop grown widely in the world. The annual global production of groundnuts has increased to approximately 50 million tons, which provides a rich source of vegetable oils and proteins for humans. Low temperature (non-freezing) is one of the major factors restricting peanut growth, yield and geographic distribution. Since the complexity of cold-resistance trait, the molecular mechanism of cold tolerance and related gene networks were largely unknown in peanut. In this study, comparative transcriptomic analysis of two peanut cultivars (SLH vs ZH12) with differential cold tolerance under low temperature (10°C) was performed using Oxford Nanopore Technology (ONT) platform. As a result, we identified 8,949 novel gene loci and 95,291 new/novel isoforms compared with the reference database. More differentially expressed genes (DEGs) were discovered in cold-sensitive cultivar (ZH12) than cold-tolerant cultivar (SLH), while more alternative splicing events were found in SLH compared to ZH12. Gene Ontology (GO) analyses of the common DEGs showed that the ‘response to stress’, ‘chloroplast part’ and ‘transcription factor activity’ were the most enriched GO terms, indicating photosynthesis process and transcription factors play crucial roles in cold stress response in peanut. We also detected a total of 708 differential alternative splicing genes (DASGs) under cold stress compared to normal condition. Intron retention (IR) and exon skipping (ES) were the most prevalent alternative splicing (AS) events. In total, 4993 transcription factors and 292 splicing factors were detected, many of them had differential expression levels and/or underwent AS events in response to cold stress. Overexpression of two candidate genes (encoding trehalose-6-phosphate phosphatases, AhTPPs) in yeast improves cold tolerance. This study not only provides valuable resources for study of cold resistance in peanut, but also lay a foundation for genetic modification of cold regulators to enhance stress tolerance in crops.